Analisis Interaksi Simbolik Waria (Wanita Transgender) di Makassar - Indonesia Timur: A Symbolic Interaction Analysis of Waria (Transgender Women) in Makassar - Eastern Indonesia - Kurniati Abidin; Yusuf Djabbar (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2019)
Transgender women (in Indonesia known as Waria) still experience social stigma and exclusion in society. This phenomenon is interesting to study because it is related to the existence of transgender women in dealing with stigma and social exclusion. This study aims to describe the way transgender women perceive social exclusion and to describe the construction of their knowledge which, despite facing social exclusion, still maintains their existence. This study used a qualitative-phenomenological study method, using a purposive sampling technique. Data collection was done by conducting observations, in-depth interviews, and documentation. Data were analyzed using qualitative descriptive using symbolic interaction theory. The results showed that transgender women perceive the stigma and social exclusion they faced was manifested by planned actions in the form of conditional neglect and delay in introducing their existence. They respond to social situations they face with adaptive and not frontal. Transgender women's knowledge construction to maintain their existence is passed through four stages, namely impulse, perception, manipulation, and completion.